“Now It's Just Old Habits and Misery”–Understanding the Impact of the Covid-19 Pandemic on People With Current or Life-Time Eating Disorders: A Qualitative Study - McCombie, Catherine; Austin, Amelia; Dalton, Bethan; Lawrence, Vanessa; Schmidt, Ulrike (Frontiers in Psychiatry, 2020)
Background: Many aspects of the Covid-19 pandemic may make living with or recovery from an eating disorder (ED) particularly challenging. Understanding the processes which underlie the psychological and behavioural responses of people with EDs during this time are key to ensure tailored support in these unprecedented circumstances. Methods: People with lifetime EDs were recruited through social media from May to June 2020 during a period of strict infection control measures in the United Kingdom (i.e., ‘lockdown’, ‘social distancing’). They completed open-ended questions in an online anonymous questionnaire that invited them to reflect on how various aspects of their lives have been affected by the Covid-19 pandemic, including ED symptoms and coping strategies. Responses were analysed using thematic analysis. Results: Most respondents reported that their ED worsened or resurfaced. Isolation, low mood, anxiety, lack of structure, disruption to routines, and media/social media messages around weight and exercise seemed to contribute to this. There was a clear sense that individuals struggled with which aspects of psychological distress to prioritise, i.e., mood versus ED cognitions and behaviours, particularly as attempts to cope with one often exacerbated the other. Nonetheless, some participants reported ‘silver linings’ of the pandemic. Conclusions: In this self-selected sample, deterioration or recurrence of ED symptoms were the norm. This has implications for the provision of treatment and care for people with EDs both in the immediate short-term and in potential future waves of the pandemic, with a significant surge of new and re-referrals expected.